2017
DOI: 10.1111/cge.13068
|View full text |Cite
|
Sign up to set email alerts
|

Novel biallelic mutations in the PNPT1 gene encoding a mitochondrial‐RNA‐import protein PNPase cause delayed myelination

Abstract: Recent studies suggest that impaired transcription or mitochondrial translation of small RNAs can cause abnormal myelination. A polynucleotide phosphorylase (PNPase) encoded by PNPT1 facilitates the import of small RNAs into mitochondria. PNPT1 mutations have been reported in patients with neurodevelopmental diseases with mitochondrial dysfunction. We report here 2 siblings with PNPT1 mutations who presented delayed myelination as well as mitochondrial dysfunction. We identified compound heterozygous mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…One of the key findings of this study is the mitochondrial import of TERC and the export of TERC-53 to the cytosol. Mitochondrial RNA import has been well established, with IMS localized protein PNPASE as a possible receptor (Mercer et al, 2011;Sato et al, 2018;Vedrenne et al, 2012;von Ameln et al, 2012;Wang et al, 2010;Zhang et al, 2014). Interestingly, PNPASE overexpression led to an accumulation of cytosolic TERC-53, but not the mitochondrial TERC-53.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key findings of this study is the mitochondrial import of TERC and the export of TERC-53 to the cytosol. Mitochondrial RNA import has been well established, with IMS localized protein PNPASE as a possible receptor (Mercer et al, 2011;Sato et al, 2018;Vedrenne et al, 2012;von Ameln et al, 2012;Wang et al, 2010;Zhang et al, 2014). Interestingly, PNPASE overexpression led to an accumulation of cytosolic TERC-53, but not the mitochondrial TERC-53.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria import a wide array of non-coding RNAs, including tRNAs, rRNAs, microRNAs, and long non-coding RNAs (lncRNAs) (Alfonzo and Sö ll, 2009;Chang and Clayton, 1989;Mercer et al, 2011;Wang et al, 2010;Zhang et al, 2014). The import of most of these RNAs depends on PNPASE, a mitochondrial IMS (intermembrane space) protein, in mammalian cells (Sato et al, 2018;Vedrenne et al, 2012;von Ameln et al, 2012;Wang et al, 2010). The functions of most imported RNAs in mitochondria, however, remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Any mutations that disrupt PNPase enzyme activity or its trimeric conformation inhibit its RNA degradation or import activities, leading to mitochondrial dysfunction and diseases. Investigations of the heterozygous variants Q254K/A510P ( 8 ) and G76D/R192* ( 10 ) will likely prove revealing, all of which are presumably defective in forming a functional trimeric PNPase.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these mutants fail to import structured RNA into mitochondria ( 6 , 7 ). Disease-linked heterozygous variants have also been identified, including Q254K/A510P that causes severe multisystem disease ( 8 ), R136H/P140L that linked to Leigh syndrome ( 9 ) and G76D/R192* (* indicating nonsense mutation) that causes delayed myelination ( 10 ). It has been shown that the mutations of R136H/P140L produced RNA degradation-inactive PNPase enzyme ( 9 ), and Q254K/A510P resulted in a lower level of PNPase that cannot assemble into a trimeric complex ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…One approach to deliver nuclear encoded RNA into mitochondria involves the utilization of a native RNA transport enzyme, polynucleotide phosphorylase (PNPase) encoded by PNPT1 gene, located in the mitochondrial inter-membranous space (26). There is increasing evidence of PNPase involved in the import of small RNAs, into mitochondria (27,28). Further, it has been shown that addition of twenty nucleotide stem-loop sequence of nuclear RNAse P, to the transcripts not normally heading to mitochondria has been shown to facilitate transportation of these RNAs into mitochondria in a PNPase-dependent manner (29).…”
Section: Introductionmentioning
confidence: 99%